IMPACT OF BASELINE DIABETES KNOWLEDGE ASSESSMENT ON BIOMARKERS IN A PILOT DIABETES EDUCATION PROGRAM - Wei, Li; Singh, Anika (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Diabetes is a pressing public health concern, with a continuous rise in its prevalence, impacting approximately 9.4% of the U.S. population. If current trends persist, projections suggest that diabetes could affect one in three U.S. adults by 2050, further emphasizing the urgency of effective glycemic management. The prevalence of diabetes escalates with age, with approximately 25.2% of individuals aged 65 or older being diagnosed. Diabetes is associated with a spectrum of complications, including retinopathy, neuropathy, and an elevated risk of cardiovascular events. Central to patient-centered glycemic management is Diabetes Self-Management Education and Support (DSMES), which is pivotal in improving outcomes and reducing healthcare costs. This form of education demonstrates several benefits, such as lowered hemoglobin A1C (A1C) levels and enhanced diabetes knowledge. Accredited DSMES programs adhere to national standards set by the American Diabetes Association and the American Association of Diabetes Educators, offering adaptable curricula to address the specific needs of participants, emphasizing the development of individualized education plans tailored to each participant's unique requirements.